PERAWATAN KELUARGA TERHADAP GANGGUAN PERTUMBUHAN ANAK TODDLER - Kartiningrum, Eka Diah; Patty, Siti Hajar; kusuma, yudha laga hadi (MEDICA MAJAPAHIT, 2024)
Growth disorders in children can be affected by a less supportive environment. Parent knowledge in necessary in process of growth in toddlers. Role of family in health and social support contributes to child growth and development process normally so that there are on disorders. Research objective wa carry out family nursing care for toddler with growth disorderin Sumbertebu Village. Design used a case study. Number of respondent were 2 people with inclusion criteria: boys and girls under 5 years old, nurtured by their biological parents. This data was collected by interview, observation and documentation techniques. Then in validation test used triangulation techniques and analyzed. Resulth of the study showed, there was diagnosis of growth disorders associated with inadequate nutrition and growth disorder associated with inability of families to recognize health problem. Intervention and implementataion conducted twice in form of providing education abaout eating pattern and good dietary. Families were able to do the health education that was given or solve existing problem so that problem was partially resolved intervention can be stopped and continued by family to be applied to the child. Growth is prosess of increasing in a person that is quantitative or increase in size. Provide information of education about good diet in toddlers, identify a good dietary menu, giving examples of healthy menus with balanced nutrition, as well as positive feedback for behavior can be done to achieve good growth in toddler